Beyond (and Before) the Transnational Turn: Recovering Civil Disobedience as Decolonizing Praxis. Issue 2 (1st December 2022) - Pineda, Erin
Abstract: Can civil disobedience be transnationalized? This question presumes civil disobedience to be a fundamentally domestic concept—one constitutively tied to both the nation-state and the normative underpinnings of liberal, constitutional democracies. This article shows how this assumption mistakes one version of civil disobedience's twentieth-century intellectual history for the whole of it, and risks reproducing binaries (domestic vs. international, democracies vs. non-democracies) that trouble attempts to theorize the transnational. Turning to an alternative intellectual history—a network of civil rights and anticolonial activists—reveals a novel theory of civil disobedience as decolonizing praxis, as well the stakes of these binaries: the disavowal of white supremacy as pervasive and durable global structure of governance, linking the domestic to the international, and democratic rule to domination.